2012
DOI: 10.1080/14786419.2012.738204
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents of Machaerium hirtum Vell. (Fabaceae) leaves and branches and its anti-inflammatory activity evaluation

Abstract: Leaves and branches of Machaerium hirtum Vell. (Fabaceae), native to South America, were subjected to phytopharmacological investigation in order to identify its major chemical constituents and evaluate its extracts, fractions and isolated compounds in assays for anti-inflammatory activities. These were performed using mouse ear edema model, pleurisy and myeloperoxidase activity assays. Six compounds were isolated and identified as the flavanones swertisin and isovitexin, the alkaloid 4-hydroxy-N-methylproline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Many chemical constituents were identified in the genus Machaerium, with the presence of several classes of compounds such as steroids, alkaloids, benzoquinones, flavonoids, terpenoids, among others (El-Sohly et al, 1999;Muhammad et al, 2001;Ignoato et al, 2012;Ribeiro et al, 2015). The plant material used in our study was chemically studied and reported by Ignoato et al (2012) and Ribeiro et al (2015).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Many chemical constituents were identified in the genus Machaerium, with the presence of several classes of compounds such as steroids, alkaloids, benzoquinones, flavonoids, terpenoids, among others (El-Sohly et al, 1999;Muhammad et al, 2001;Ignoato et al, 2012;Ribeiro et al, 2015). The plant material used in our study was chemically studied and reported by Ignoato et al (2012) and Ribeiro et al (2015).…”
Section: Resultsmentioning
confidence: 99%
“…In the preliminary research conducted by Ignoato et al (2012), five pure compounds produced by this legume were extracted and identified from the material used here. The steroids stigmasterol (24α-ethyl-cholest-5,22-dienol) and β-sitosterol (24α-ethyl-cholest-5-enol) were found in leaf FH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations